Craig Of the Creek: Black childhood and environmental racism. Issue 5 (20th October 2022) - Thomas, Alex
ABSTRACT: The animated show Craig of the Creek is an important source of animated environmental imagery for children as its main characters and plot provide the opportunity to discuss both race and environmental issues. However, these shows often only show one view of environmental degradation and ignore issues like environmental racism and urban housing issues. The history of racial environmental innocence and the exclusion of people of color need to be considered to fully understand the benefits and shortcomings of the show's narrative. I argue that while Craig of the Creek resists some notions of racial innocence, the show still promotes a mainly romanticized, commodified view of nature. To do this, I provide a close ecocritical analysis utilizing discourse analysis and environmental racism theory to explain how well the show includes social inequality. I conclude that while the cartoon acknowledges pollution and the dangers of nature, it largely ignores the complicated relationship between race and the environment and reproduces the idea of the environment being nothing more than a commodity. It glosses over the complicated history that both people of color and indigenous people have with nature ownership and is passing on an unfortunate lesson to children viewing the program.